Frequency and Prognostic Impact of ALK Amplifications and Mutations in the European Neuroblastoma Study Group (SIOPEN) High-Risk Neuroblastoma Trial (HR-NBL1) - Bellini, Angela; Pötschger, Ulrike; Bernard, Virginie; Lapouble, Eve; Baulande, Sylvain; Ambros, Peter F; Auger, Nathalie; Beiske, Klaus; Bernkopf, Marie; Betts, David R; Bhalshankar, Jaydutt; Bown, Nick; et al. (Journal of clinical oncology, 2021)
PURPOSE: In neuroblastoma (NB), the ALK receptor tyrosine kinase can be constitutively activated through activating point mutations or genomic amplification. We studied ALK genetic alterations in high-risk (HR) patients on the HR-NBL1/SIOPEN trial to determine their frequency, correlation with clinical parameters, and prognostic impact. MATERIALS AND METHODS: Diagnostic tumor samples were available from 1,092 HR-NBL1/SIOPEN patients to determine ALK amplification status (n = 330), ALK mutational profile (n = 191), or both (n = 571). RESULTS: Genomic ALK amplification (ALKa) was detected in 4.5% of cases (41 out of 901), all except one with MYCN amplification (MNA). ALKa was associated with a significantly poorer overall survival (OS) (5-year OS: ALKa [n = 41] 28% [95% CI, 15 to 42]; no-ALKa [n = 860] 51% [95% CI, 47 to 54], [P < .001]), particularly in cases with metastatic disease. ALK mutations (ALKm) were detected at a clonal level (> 20% mutated allele fraction) in 10% of cases (76 out of 762) and at a subclonal level (mutated allele fraction 0.1%-20%) in 3.9% of patients (30 out of 762), with a strong correlation between the presence of ALKm and MNA (P < .001). Among 571 cases with known ALKa and ALKm status, a statistically significant difference in OS was observed between cases with ALKa or clonal ALKm versus subclonal ALKm or no ALK alterations (5-year OS: ALKa [n = 19], 26% [95% CI, 10 to 47], clonal ALKm [n = 65] 33% [95% CI, 21 to 44], subclonal ALKm (n = 22) 48% [95% CI, 26 to 67], and no alteration [n = 465], 51% [95% CI, 46 to 55], respectively; P = .001). Importantly, in a multivariate model, involvement of more than one metastatic compartment (hazard ratio [HR], 2.87; P < .001), ALKa (HR, 2.38; P = .004), and clonal ALKm (HR, 1.77; P = .001) were independent predictors of poor outcome. CONCLUSION: Genetic alterations of ALK (clonal mutations and amplifications) in HR-NB are independent predictors of poorer survival. These data provide a rationale for integration of ALK inhibitors in upfront treatment of HR-NB with ALK alterations.
Keywords: Randomized Controlled Trials as Topic; Mutation Rate; Female; Europe; Infant; předškolní dítě; ženské pohlaví; protoonkogen n-myc; anaplastická lymfomová kináza; lidé; Evropa; Anaplastic Lymphoma Kinase; klinické zkoušky, fáze III jako téma; následné studie; míra přežití; mutační rychlost; prognóza; Risk Factors; Follow-Up Studies; Gene Amplification; Male; kojenec; Child, Preschool; randomizované kontrolované studie jako téma; rizikové faktory; Neuroblastoma; Prognosis; Clinical Trials, Phase III as Topic; N-Myc Proto-Oncogene Protein; Survival Rate; neuroblastom; mužské pohlaví; amplifikace genu; Humans